Rotary mechanism of the prokaryotic Vo motor driven by proton motive force - Jun-ichi Kishikawa; Yui Nishida; Atsuki Nakano; Takayuki Kato; Kaoru Mitsuoka; Kei-ichi Okazaki; Ken Yokoyama (Nature Communications)
Abstract ATP synthases play a crucial role in energy production by utilizing the proton motive force (pmf) across the membrane to rotate their membrane-embedded rotor c-ring, and thus driving ATP synthesis in the hydrophilic catalytic hexamer. However, the mechanism of how pmf converts into c-ring rotation remains unclear. This study presents a 2.8 Å cryo-EM structure of the Vo domain of V/A-ATPase from Thermus thermophilus, revealing precise orientations of glutamate (Glu) residues in the c 12-ring. Three Glu residues face a water channel, with one forming a salt bridge with the Arginine in the stator (a/Arg). Molecular dynamics (MD) simulations show that protonation of specific Glu residues triggers unidirectional Brownian motion of the c 12-ring towards ATP synthesis. When the key Glu remains unprotonated, the salt bridge persists, blocking rotation. These findings suggest that asymmetry in the protonation of c/Glu residues biases c 12-ring movement, facilitating rotation and ATP synthesis.